Importance of care in the farrowing unit and during the first 24 hours of piglets' lives - Maldaner, Vitória Helena; Perosa, Manuela Louise (Seven Editora, 2024)
Pork is among the most consumed sources of animal protein not only in Brazil, but also in the world, which generates a progressive intensification of this activity, to meet the demand and requirements of the consumer market. Brazil occupies the fourth position in the world ranking of pork production, which reveals the importance of this activity in the country's livestock sector. The indices indicate an even more gradual growth for the following years and in order for this to actually occur, it is of paramount importance to carry out the proper management of the animals, especially in the farrowing and piglet phase. DOI:https://doi.org/10.56238/sevened2024.001-037